2015
DOI: 10.1002/jbm.a.35501
|View full text |Cite
|
Sign up to set email alerts
|

Biological responses of preosteoblasts to particulate and ion forms ofCo‐Cr alloy

Abstract: This study compared the particulate and ion forms of a cobalt-chrome (Co-Cr) alloy on the differentiation/activation of preosteoblasts. Mouse preosteoblasts (MC3T3-E1) were cultured in an osteoblast-induction medium in the presence of particulate and ion forms of a Co-Cr alloy, followed by cell proliferation and cytotoxicity evaluations. The maturation and function of osteoblasts were assessed by alkaline phosphatase (ALP) assay and related gene expressions. Both particulate and ion forms of the metals signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…31 It is therefore estimated that local Co(II) levels may be as high as 0.50 – 1 mM, implying that the concentrations utilized in this study were within a clinically significant range. 32 Further, our preliminary in vitro test 33 clearly suggested that particles (5 mg/ml) or ions (1mM) resulted in ubiquitous cell death compared to debris-free controls, while particles﹤0.15 mg/ml or ions ﹤32 μM did not show any influence on preosteoblast proliferation. We then determined to use particles concentrations at 0.3 and 2.5 mg/ml, in comparison with the metal ions at 62 and 500μM as physiological and clinical relevant low and high concentrations for the current study.…”
Section: Discussionmentioning
confidence: 88%
“…31 It is therefore estimated that local Co(II) levels may be as high as 0.50 – 1 mM, implying that the concentrations utilized in this study were within a clinically significant range. 32 Further, our preliminary in vitro test 33 clearly suggested that particles (5 mg/ml) or ions (1mM) resulted in ubiquitous cell death compared to debris-free controls, while particles﹤0.15 mg/ml or ions ﹤32 μM did not show any influence on preosteoblast proliferation. We then determined to use particles concentrations at 0.3 and 2.5 mg/ml, in comparison with the metal ions at 62 and 500μM as physiological and clinical relevant low and high concentrations for the current study.…”
Section: Discussionmentioning
confidence: 88%
“…Although PMMA and CE particles behave similarly to Ti [34,49], ZrO 2 reduced pro-inflammatory genes more than Ti [54]. The addition of Ni to Co-Cr-Mo alloys reduced gene for TNFα [1] and Co-Cr alloy increased osteoclastogenesis to a greater extent than the ion form [40]. …”
Section: Discussionmentioning
confidence: 99%
“…Mouse macrophage cell lines (RAW264.7) were the most used [4,6,27,28,29,30,31,32,33,34,35,36,37], followed by OB precursors derived from mouse calvaria (MC3T3-E1) [27,28,38,39,40,41] and human (Saos-2 and MG-63) [1,42,43] or rat (ROS 17/2.8) [44] osteosarcoma and monocitic (THP-1) [20,45,46] cell lines. In addition, other studies also used primary cells: mouse [28,47] or human [42,48] OBs, mouse or rat bone-marrow-derived macrophages (BMM) [28,49,50,51], human MSCs [39,52], mouse [47] or human [53] FBs and mouse peritoneal macrophages [54].…”
Section: Gene Expression In Osteolysismentioning
confidence: 99%
See 2 more Smart Citations